Sixteen Years' Result of Posterior-Stabilized TKA - Wing, Cheung Kin; Kwok-Hing, Chiu (The Journal of Knee Surgery, 2012)
Total knee arthroplasty (TKA) had been reported to have excellent result; however, most of the publications reported either mixed cruciate retaining and posterior-stabilized prostheses or mixed patient groups of rheumatoid arthritis and primary osteoarthritis. The long-term result of posterior-stabilized TKA in primary osteoarthritis has rarely reported. From 1994 to 2001, the survival of 179 posterior-stabilized TKAs (Insall-Burstein II, Zimmer, Warsaw, IN) in 146 patients with primary osteoarthritis was studied. The survival using revision surgery for aseptic loosening as end point and the potential prognostic factors (gender, age <65 years old, activity level, body mass index) were studied. The 10 and 16.4 years survival using revision surgery for aseptic loosening as end point were 97.7 and 94.8%, respectively. Seven knees were revised for aseptic loosening with mechanical failure rate of 3.9%. No significant prognostic factor for the long-term survival of posterior-stabilized TKA was identified. The long-term survival of the posterior-stabilized TKA was comparable with cruciate retaining and mobile bearing TKA in primary osteoarthritis.
Keywords: total knee arthroplasty; posterior-stabilized total knee arthroplasty; survival; young; outcome; result